2003
DOI: 10.1007/s00464-002-8874-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of laparoscopic versus open resections for rectal cancer for 124 unselected patients

Abstract: Oncologic surgical principles were respected. Long-term outcome after laparoscopic resection of rectal cancer was comparable with that after conventional resection. We should wait to draw conclusive scientific statements until the completion of ongoing international randomized controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(70 citation statements)
references
References 26 publications
9
55
1
5
Order By: Relevance
“…Feliciotti et al prospectively studied laparoscopic assisted and open resections and found both methods to respect oncologic principles with similar long-term outcomes. 21 Prospective studies have revealed that laparoscopic resection compared with open surgery did not worsen survival or disease control in patients with rectosigmoid cancer. 2 recent meta-analysis reviewed the current literature on the laparoscopic resection of rectal cancer.…”
Section: Prospective Randomized Controlled Trials: Long-term Results mentioning
confidence: 99%
“…Feliciotti et al prospectively studied laparoscopic assisted and open resections and found both methods to respect oncologic principles with similar long-term outcomes. 21 Prospective studies have revealed that laparoscopic resection compared with open surgery did not worsen survival or disease control in patients with rectosigmoid cancer. 2 recent meta-analysis reviewed the current literature on the laparoscopic resection of rectal cancer.…”
Section: Prospective Randomized Controlled Trials: Long-term Results mentioning
confidence: 99%
“…En el análisis univariado, la necesidad de transfusión de glóbulos rojos en el intraoperatorio y la edad sobre 75 años, fueron los factores que resultaron significativos con un OR de 8,36 (3,18) y 1,79 (1,(1)(2)(3)20) respectivamente. Los factores que no resultaron significativos pero que se consideraron para el análisis multivariado fueron el puntaje ASA III o IV, el IMC, el tiempo operatorio y la cirugía de urgencia (Tabla 5).…”
Section: Resultsunclassified
“…Numerosas publicaciones han demostrado las ventajas del abordaje laparoscópico en cuanto a menor necesidad de analgésicos, menor tiempo de estadía hospitalaria, menor tiempo de reinicio de actividades regulares y menor infección de sitio quirúrgico [1][2][3][4][5] . Sin embargo, el abordaje mínimamente invasivo no está exento de complicaciones, su morbilidad descrita va entre un 6 y un 30% y la mortalidad entre 0 y 4,5% 6 .…”
Section: Factores Asociados a Morbilidad Precoz En Cirugía Colorrectaunclassified
“…Feliciotti et al 89 prospectively studied LARR and open resections and found both methods respected surgical oncologic principles, with similar long-term outcomes. Additional studies have mimicked these results.…”
Section: Laparoscopic Resection For Rectal Cancermentioning
confidence: 96%